Proliferation and migration of ML1 follicular thyroid cancer cells are inhibited by IU1 targeting USP14: role of proteasome and autophagy flux - Srinivasan, Vignesh; Asghar, Muhammad Yasir; Zafar, Sadia; Törnquist, Kid; Lindholm, Dan (Frontiers in Cell and Developmental Biology, 2023)
USP14 is a deubiquitinating enzyme involved in protein degradation by interacting with the proteasome and removal of poly-ubiquitin chains on target proteins. USP14 can influence cellular processes such as cell survival, DNA repair, ER stress, endocytosis, and the inflammatory response. USP14 further plays a role in tumor growth, and the inhibition of USP14 by compounds such as IU1 may affect cancer cell migration and invasion. Here we have studied the mechanisms for the action of IU1 in ML1 follicular thyroid cancer cells, comparing them with control, primary thyroid cells. Treatment with IU1 reduced proliferation of ML1 cells in a concentration-dependent manner, and more prominently than in control cells. IU1 decreased basal migration of ML1 cells, and after stimulation of cells with the bioactive compound, sphingosine-1-phosphate. The sphingosine-1-phosphate receptor 3 was increased in ML1 cells as compared with control thyroid cells, but this was not influenced by IU1. Further studies on the mechanism, revealed that IU1 enhanced the proteasome activity as well as LC3B-dependent autophagy flux in ML1 cells with an opposite effect on control thyroid cells. This indicates that IU1 elicits a cell-type dependent autophagy response, increasing it in ML1 cancer cells. The IU1-mediated stimulation of autophagy and proteasomes can likely contribute to the reduced cell proliferation and migration observed in ML1 cells. The precise set of proteins affected by IU1 in ML1 thyroid and other cancer cells warrant further investigations.